A scoring system for euthanasia decisions in rescued raccoon dogs (Nyctereutes procyonoides): Standardized criteria in wildlife rehabilitation - Bong Kyun Kim; Soo Hyung Eo (PLoS ONE, 2026)
Wild animal rescue and control centers routinely encounter situations that require evaluating a rescued animal’s potential for recovery and making decisions on appropriate treatment, rehabilitation, or euthanasia. However, currently, scientific standards to guide these decisions are lacking, and frequent reliance on empirical judgment leads to application of subjective criteria for euthanasia. Therefore, this study aimed to analyze factors affecting rescue outcomes in 1,376 raccoon dogs rescued by the Chungnam Wild Animal Rescue Center over 13 years, to predict the likelihood of release, and to develop a system to inform euthanasia decisions. The model that best predicted the release of rescued raccoon dogs included the cause of the accident, season, and level of injury. Based on this, a scored assessment support system was constructed, and raccoon dogs were classified into a ‘low-risk group,’ requiring active treatment and rehabilitation owing to the high likelihood of live release, a ‘medium-risk group,’ requiring mid-to-long-term euthanasia decisions through close monitoring and re-assessment, and a ‘high-risk’ group, for which immediate euthanasia may be considered because of the extremely low probability of release. The proposed scoring-based euthanasia decision support system integrates clinical and situational factors and remains practical by relying on data that can be readily obtained in the field immediately after rescue. Therefore, by supporting rapid, consistent decision-making and using basic data to prepare standardized euthanasia guidelines, this system can improve animal welfare and operational efficiency.